2022
DOI: 10.1364/oe.438876
|View full text |Cite
|
Sign up to set email alerts
|

Confidence map tool for gradient-based X-ray phase contrast imaging

Abstract: We present a graphical tool that we call a "confidence map". It allows to evaluate locally the quality of a phase image retrieved from the measurement of its gradients. The tool is primarily used to alert the observer to the presence of artifacts that could affect his interpretation of the image. It can also be used to optimize a phase imager since it associates a cause with the creation of each artifact: dislocation, under-sampling and noise. An illustration of the use of the confidence map tool is presented,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The quality of the OPD image reconstruction in CGM was also studied recently by Stolidi et al in the X-ray spectral range [43]. The authors introduced a so-called confidence map, stemming from the PDCM 𝐶 defined by Eq.…”
Section: Truenessmentioning
confidence: 98%
“…The quality of the OPD image reconstruction in CGM was also studied recently by Stolidi et al in the X-ray spectral range [43]. The authors introduced a so-called confidence map, stemming from the PDCM 𝐶 defined by Eq.…”
Section: Truenessmentioning
confidence: 98%
“…The quality of the OPD image reconstruction in CGM was also studied recently by Stolidi et al, in the X-ray spectral range [42]. The authors introduced a so-called confidence map, stemming from the PDCM C defined by Eq.…”
Section: Truenessmentioning
confidence: 98%
“…CGM is also used in other spectral domains, like in the X-rays [41]. Recently Stolidi et al reported possible accuracies using CGM (named multiwave shearing interferometry, or grating interferometry in this context), and a confidence map that allows an estimation of the phase reconstruction quality, and the occurrence of artifacts [42].…”
Section: Truenessmentioning
confidence: 99%
“…Si on regarde un point de la surface d'onde à reconstruire (figure 3, droite), on voit qu'on peut faire une circulation : on prend la valeur de la dérivée en x pour se propager du point A au point B, puis la valeur de la dérivée en y pour monter du point B au point C, moins la dérivée en x entre les points C et D, et enfin, moins la dérivée en y pour revenir au point d'origine A. Comme la mesure est entachée d'un certain bruit, la position de retour ne sera pas strictement superposée avec l' origine. En estimant de façon systématique ces circulations en tous points de la surface reconstruite, il est donc possible de déduire une cartographie des écarts-type de l'erreur de mesure des dérivées à partir de la mesure elle-même [5].…”
Section: Un Traitement De Fourier Naturelunclassified